mathdad
Full Member
- Joined
- Apr 24, 2015
- Messages
- 925
Solve the inequality.
x^2 + x > 12
Solution:
x^2 + x - 12 > 0
x^2 + x - 12 = 0
(x - 3)(x + 4) = 0
x = 3, x = - 4
Pick a number between 3 and -4.
Let x = 0
x^2 + x - 12 > 0
(0)^2 + 0 - 12 > 0
-12 > 0...false statement.
I conclude that the solution for the given quadratic inequality is found in the following intervals:
(-infinity, -4) (3, infinity)
Correct?
x^2 + x > 12
Solution:
x^2 + x - 12 > 0
x^2 + x - 12 = 0
(x - 3)(x + 4) = 0
x = 3, x = - 4
Pick a number between 3 and -4.
Let x = 0
x^2 + x - 12 > 0
(0)^2 + 0 - 12 > 0
-12 > 0...false statement.
I conclude that the solution for the given quadratic inequality is found in the following intervals:
(-infinity, -4) (3, infinity)
Correct?